When Corporations Substitute for Adversarial Unions: Labour Markets and Human Resource Management at Magna - Lewchuk, Wayne; Wells, Don (Relations industrielles / Industrial Relations, 2006)
The industrial relations system at Magna International is an example of an integrated, coherent, non-union human resource management strategy. It includes significant mechanisms of worker voice and conflict resolution as substitutes for union representation. Potential labour-management conflicts associated with Taylorized labour processes are often translated into group problem-solving. Redistributive conflicts are re-framed as mutual gains through profit-sharing. Corporate communications promote an ethos of competitiveness. Individualized pay and promotion schemes, segmented internal labour markets, and the exposure of individual plants to competitive pressures, promote cultures of labour cooperation in the pursuit of productivity gains. The success of this union avoidance model is situated in a context of the erosion of unionized labour relations, the disciplinary effects of precarious labour markets, and the vulnerability of workplaces to transnational competitive forces. Continued success is predicated on Magna’s ability to survive sectoral and macroeconomic restructuring forces which are, in large measure, beyond management’s control.